Android-based P2P file sharing over zigBee radios - Abd Rahman, Akmal Nurhananie; Habaebi, Mohamed Hadi; Ismail, Mahamod (2014)
The peer-to-peer (P2P) file sharing protocol has evolved from depending on Internet connection provided by traditional mobile cellular telecommunication networks to free Internet connectivity through Wi-Fi technology. Recently, P2P reach was extended further in the Personal Area Network using Bluetooth. On the other hand, IEEE 802.15.4 Zigbee is a wireless sensor network (WSN) standard and smart phones are expected to be equipped with a ZigBee modem to provide control functionality for personal WSNs such as home networking, body area networks, …etc. This paper introduces ZigBee technology to the mobile P2P environment, involving devices with Android 4.0 (Ice Cream Sandwich) and higher OSs. Such an Android platform is the lowest version that can be found among smartphones, tablets, and more. Results show that the developed protocol provides P2P and P2MP functionality between devices supporting Zigbee air interface.